Composição do óleo essencial da laranjeira ‘pera’ [Citrus sinensis (L) Osbeck] em diferentes porta-enxertos: bioatividade a Aceria guerreronis keifer (Acari: Eriophyidae) e seletividade a inimigo natural - Brito, Dalton Rodrigues Barros (2020)
Citrus essential oils (EOs) are bioactive to an array of phytophagous arthropods. Despite the increasing number of varieties to genetically diversfy the orchards, little is known about the influence of the rootstock on the composition and bioactivity of EOs in the scion varieties. Thus, this study aimed at identifying the chemical composition of EOs extracted from the ‘Pera’ sweet orange [Citrus sinensis (L). (Osbeck], the most cultivated variety in the citrus growing area of Bahia and Sergipe, grafted on ten rootstocks, assessing its bioactivity to coconut mite Aceria guerreronis Keifer (Acari: Eriophyidae) and compatibility with the predatory mite Typhlodromus ornatus Denmark & Muma (Acari: Phytoseiidae). The EO extracted from the leaves of the ten rootstocks presented the same chemical profile, namely: sabinene (30,47-34,17%) as major component, followed by δ-3-carene (7,78-12,4%) and (E) -ȕ-ocimene (8.04- 10,46%). The EO extracted from leaves of ‘Pera’ sweet orange grafted on ‘Rangpur’ lime was selected to assess the lethal toxicity to coconut mite and to evaluate the compatibility of this EO with the predatory mite. This oil was selected because these combination scion – rootstock is widely cultivated in the study region. The LC50 (4,28 mg/mL) and LC80 (10,39 mg/mL) were estimated for A. guerreronis, however these LCs did not cause mortality to T. ornatus. The LC80 of the EO did not repel A. guerreronis and the temporal toxicity of the same LC occurred only in the first hours of exposure (<3h). The LC80 of the EO, estimated for A. guerreronis, did not affect the predator's growth rate. Thus, the EO obtained from ‘Pera’ sweet orange presented bioactivity to the coconut mite A. guerreronis and compatibility with the predatory mite T. ornatus.